Implementasi Peningkatan Mutu Pendidikan dengan Pendekatan Total Quality Manajemen - Syamsy, Badrus; Fauzan, Umar; Malihah, Noor (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Competition in the quality of education has become a driving force for educational institutions to enhance their quality in order to compete in society. Just like what has been done by Fastabiqul Khairat Elementary School in Samarinda, they have been focusing on improving the management of educational quality. Therefore, this research aims to examine the improvement of educational quality carried out by Fastabiqul Khairat Elementary School in Samarinda. The research method used in this study is qualitative with a case study approach. Data sources were obtained from observations, interviews, and documentation. The data analysis technique used was interactive, which involved data condensation, data presentation, and drawing conclusions. The results of this study show that Fastabiqul Khairat Elementary School in Samarinda has improved its educational quality through the implementation of the Total Quality Management (TQM) approach. The school's approach to improving educational quality differs from other Islamic-oriented schools. This can be seen in its strategic management, which involves organizing programs and establishing professional relationships with external parties. Continuous improvement is also prioritized, such as emphasizing the professionalism of educators in their respective fields. Language instruction, for example, is conducted by specialized instructors, and teachers are equipped to enhance their professionalism both at the local and international levels. The school also collaborates with the Cambridge curriculum to enhance the quality of learning. Adequate facilities and infrastructure are provided to support students' mastery of both soft and hard skills. The school values input from students and parents, actively seeking and incorporating their suggestions. Based on these factors, the management practices implemented by Fastabiqul Khairat Elementary School in Samarinda can serve as a model for other schools aiming to enhance the quality of education through Total Quality Management approaches.